Urgensi Pengaturan Aksesabilitas Atas Layanan Perbankan Syariah Bagi Penyandang Disabilitas - Arifah, Risma Nur (Sakina: Journal of Family Studies, 2022)
The purpose of this study is to identify the factors that have not fulfilled the access rights of persons with disabilities to sharia banking services in Malang City and legal efforts to identify these problems. The type of research used is juridical empirical with a conceptual approach, statue approach and sociological juridical. The data collection method was done by means of open interviews and documentation. The results show that, first, there are no factors that cause the access rights of persons with disabilities to banking services have not been fulfilled 1) legal factors, juridically, the laws and regulations in the banking sector do not clearly regulate the rights of access to banking services in general, but these regulations are listed in POJK Number 76 / POJK.07 / 2016; 2) law enforcement factors, OJK has not effectively provided supervision of facilities for persons with disabilities in sharia banking so that facilities for customers with disabilities in several banks are still considered the same as non-disabled customers; 3) low financial literacy and education for persons with disabilities, so they choose not to use banking services to save money. Second, the legal remedies that have been taken against the fulfillment of sharia banking services in Malang are 1) forming a National Disability Commission; 2) provide financial education or legal literacy.